Qualidade do solo em cultivos consorciados de fava em agroecossistemas familiares no agreste da Paraíba - Santos, Fabiana do Nascimento (2015)
Crop systems can cause significant changes in soil attributes. As a result, the effects of management on soil quality in areas where natural vegetation has been replaced by annual crops have received attention and studies. The objective of this study was to evaluate soil quality in fava (Phaseolus lunatus) production systems in family farming agroecosystems under different growing periods, in two soil classes. The research was conducted in areas with lima bean cropping in diversified production systems, located in the municipalities of Areia (Argisol) and Queimadas (Vertisol), in the micro-region of Agreste of Borborema, state of Paraíba, Brazil. The first chapter describes a socioeconomic diagnosis of lima bean production carried out through a semi-structured interview with the family farmers of four municipalities in the micro-region. Data was processed through descriptive analysis. The soil quality assessment method consisted in laboratory determination of soil chemical, physical and biological attributes of samples collected in the 0-5, 5-10 and 10-20 cm depths. In each soil class, the Soil Quality Index (IQS) was obtained from the deviations of the soil attributes in the different production systems in relation to the soil in the area under native vegetation. Of the farmers interviewed, 100% grow lima bean in an intercropping system, mainly with corn; 50% of the farmers cultivate lima bean more than five cropping cycles in the same area; while 82% of the farmers fertilize the soil with the incorporation of lima bean residues and cattle manure obtained by grazing. In the Agreste of Borborema lima bean is cropped exclusively in family farmer agroecosystems. In both soils and in the lima bean crop systems sampled, the IQS varied from poor (< 0.50) to average (> 0.50 < 0.70). The soil quality index was efficient in reflecting changes in soil attributes evaluated in the crop production systems, as compared to the native vegetation area, and could be used to monitor the sustainability of lima bean production systems.